DISTANCING FROM HISTORICAL ACHIEVEMENTS: PEDAGOGICAL PRACTICE IN EARLY YEARS EDUCATION DURING COVID 19 PANDEMICS - Magalhaes, Cassiana; Lazaretti, Lucineia Maria; Pasqualini, Juliana Campregher [UNESP] (Fundacao Univ Tocantins, 2021)
This article seeks to register, systematize and synthesize the main issues that arose within the universe of early childhood education in the scenario of the coronavirus pandemic (Covid-19). The objective is to contribute to draw an outline of this period and accumulate subsidies for a future assessment of the effects and consequences of the social and political conduct of the difficulties and dilemmas that arose for early childhood education in the situation of pandemic exceptionality. Considering the activity of the teacher and the activity of the child within the pedagogical activity, it is argued that the choices and actions of this period confined early childhood education to meeting formal, protocol and bureaucratic demands, and distanced it from its humanizing and developmental societal responsibility. The imperative of reinventing oneself, in such a scenario, seems to have fulfilled the ideological function of hiding the absence of conditions and social and institutional support.
Keywords: Pedagogical activity; Early childhood education; Pandemics